The Effect of Health Promotion Model and Self Determination Theory Based Intervention on Anemia Prevention Behavior and Haemoglobin Level in Pregnant Women - Mira Triharini; Agus Sulistyono; Merryana Adriani; Shrimarti Rukmini Devy (Jurnal Ners, 2019)
Introduction: Anemia during pregnancy has an impact on pregnancy and fetus. The low status of prenatal iron in pregnant women may also affect neurodevelopment and behavior in children. Many pregnant women still do not have good behaviors in preventing anemia. The objective of the study was to analyze the effect of Health Promotion Model and Self Determination Theory Based Intervention on anemia prevention behaviors and haemoglobin level in pregnant mothers.Methods: This research was a quasi-experiment research with a pre- and post-test using a control group design. The samples were 30 pregnant women who did antenatal care in Community Health Center of Tanah Kali Kedinding Surabaya. Data were collected using questionnaires, food recall in 2x24 hours, and haemoglobin level examination using the cyanmethaemoglobin method.Results: There was an effect of Health Promotion Model and Self Determination Theory Based Intervention to anemia prevention behaviors and haemoglobin level (p = 0.013; p = 0.040).Conclusion: Health Promotion Model and Self Determination Theory Based Intervention improve the anemia prevention behaviors and haemoglobin level. Health workers can use Health Promotion Model and Self Determination Theory Based Intervention to improve anemia prevention behavior